Contribution of the retronasal odor of soy sauce to salt reduction. Issue 8 (11th July 2020) - Manabe, Mariko; Sakaue, Ryoichi; Obata, Akio
Abstract : Abstract: The characteristic odor of soy sauce has been reported to enhance saltiness. However, soy sauce is used not only as a sauce that is added directly to food, but also as a seasoning. In addition, some of the aromatic compounds that contribute to the soy sauce odor change during cooking or heating. In the present study, the effects of the retronasal odor of uncooked and cooked soy sauce on the enhancement of saltiness and palatability of a low‐salt solution were sensory evaluated. A probit analysis indicated that the saltiness‐enhancing effect of the odor of 15% uncooked soy sauce was lost by heating. The odors of soy sauce boiled for 10 min (cooked SS) and the residue of soy sauce heated at 200 °C for 1 min improved the palatability of the low‐salt solution. Gas chromatography (GC) analyses, namely, GC–olfactometry and GC–mass spectrometry, showed that one active candidate aromatic component of soy sauce contributing to saltiness enhancement was 3‐methyl‐1‐butanol (3‐Me‐BuOH). The saltiness‐enhancing effects of cooked SS could be restored by adding 3‐Me‐BuOH, as assessed by the sensory evaluation. These data demonstrated that 3‐Me‐BuOH contributes to saltiness enhancement. Practical Application: We found that the odor of cooked soy sauce could improve the palatability of low‐salt food. Although the saltiness‐enhancing effect provided by the odor of uncooked soy sauce was lost, the saltiness‐enhancing effect of the odor of cooked soy sauce can be partially restored by adding 3‐methyl butanol. Thus, not only the odor of unheated soy sauce but also the odor of heated soy sauce following addition of 3‐methyl butanol may be useful for developing palatable salt‐reduced food.